The meddlers sovereignty, empire, and the birth of global economic governance - Martin, Jamie (Cambridge, Massachusetts Harvard University Press, 2022)
While the birth of global economic governance is conventionally dated to the end of World War II, Jamie Martin shows how its roots lie in World War I and its aftermath. The Meddlers explores the intense political struggles about sovereignty and self-governance provoked by the first attempts to govern global capitalism
345p.;24cm
Keywords: International Monetary Fund--History.